2017
DOI: 10.5194/isprs-annals-iv-2-w4-35-2017
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Single Tree Stems in Forested Areas From High Density Als Point Clouds Using 3d Shape Descriptors

Abstract: ABSTRACT:Airborne Laser Scanning (ALS) is a widespread method for forest mapping and management purposes. While common ALS techniques provide valuable information about the forest canopy and intermediate layers, the point density near the ground may be poor due to dense overstory conditions. The current study highlights a new method for detecting stems of single trees in 3D point clouds obtained from high density ALS with a density of 300 points/m 2 . Compared to standard ALS data, due to lower flight height (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In a forest environment, Polewski et al [38] proposed an approach that combined a point-based and a segment-based method to detect fallen tree stems from TLS datasets. Amiri et al [39] applied Polewski 's method to detect tree stems from very-high density airborne laser scanning datasets. However, they employed a supervised method in the stage of point-based classification by using multiple features, which increased the complexity of the algorithm and turned out to be a time-consuming approach.…”
Section: Introductionmentioning
confidence: 99%
“…In a forest environment, Polewski et al [38] proposed an approach that combined a point-based and a segment-based method to detect fallen tree stems from TLS datasets. Amiri et al [39] applied Polewski 's method to detect tree stems from very-high density airborne laser scanning datasets. However, they employed a supervised method in the stage of point-based classification by using multiple features, which increased the complexity of the algorithm and turned out to be a time-consuming approach.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years several methods for extracting tree stems using ALS have been developed [1,[18][19][20][21][22][23]. Due to differing objectives, differing ALS acquisition designs and differing investigated forest types and structures, the accuracy of the trunk detection methods is hard to compare.…”
Section: Stem Detection Using Alsmentioning
confidence: 99%
“…Amiri et al [21] enhance the method of Polewski et al [19] for identifying individual tree stems using high density ALS point clouds. With a Random Forest Classifier, points associated with tree stems are classified using 3D shape descriptors, covariance features and the normalized height.…”
Section: Stem Detection Using Alsmentioning
confidence: 99%
“…Their results showed that downed dead wood volume was automatically estimated with an RMSE of 15.0 m 3 /ha (59.3%), which was reduced to 6.4 m 3 /ha (25.3%) when visual interpretation was incorporated. In another study, Amiri et al [26] used visual interpretation to identify all the reference stems, and they compared them with stems obtained through laser scanning. The evaluation of the automatically detected stems showed a classification precision of 0.86 and 0.85 and recall values of 0.7 and 0.67 for plots 1 and 2, respectively.…”
Section: Introductionmentioning
confidence: 99%